“What Is PER?” Patient Engagement in Research as a Hit - Bélisle-Pipon, Jean-Christophe; Del Grande, Claudio; Rouleau, Geneviève (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
Engaging patients in research conduct and agenda setting is increasingly considered as an ethical imperative, and a way to transcend views of patients as passive subjects by fostering their empowerment. However, patient engagement in research (PER) is still an emerging approach with debated definitional and operational frameworks. This song addresses the sometimes difficult encounter and elusive mutual understanding between researchers and patients. “What is PER?” is an impressionistic illustration of the challenges and issues that can be found in the universe of patient engagement in research.